Flödeskalibrering : Analys av kalibreringsprocesser - Björnström, Albert (Luleå tekniska universitet, Drift, underhåll och akustik, 2018)
In December 2015 the Paris Agreement was signed in order to create a better global climate. According to the agreement, all countries 'emissions shall be reported to the UN. To be able to do this current emission levels must be known, which means measurement and calculation of emissions are necessary. The state-owned mining company Luossavaara Kiirunavaara AB (LKAB) operates iron ore mines in Northen Sweden. The iron ore products produced at the KK4 coal mill in Kiruna, consists of some additives that form carbon dioxide when burned. The amount of additives burned is measured using two flowmeters. To ensure that these meters have approved accuracy, annual calibrations are performed where measured volume is compared to a reference volume. In order to ensure that LKAB's calibration method works, another type of calibration was performed by an external company. The results between the two calibration methods differ significantly, which led to this report. The purpose of this work is to develop improvement proposals for LKAB's calibration method and to present suggestions on how LKAB can create better conditions for the other so called transit time calibration method. By analyzing each method and performing measurements, tests and calculations, weaknesses are noted. Tests show that a weakness of LKAB's calibration is that the level measurement method used is person-dependent. Level measurement with laser range gauge is tested with good results, why this type of measurement is recommended in the future. The main weakness with transit time method is primarily that it is sensitive to variation of the inner diameter of the pipe. In order for this method to provide reliable results, rebuilding of pipes and carefully measured internal diameter are required. Accurate flow measurement means that current carbon dioxide emissions can be calculated, which enables continued work towards set environmental goals. Flowmeters also have a significant role in product quality in KK4, which means that this report can contribute to ...